MENINGKATKAN HASIL BELAJAR IPA MELALUI PENERAPAN STRATEGI PEMBELAJARAN INKUIRI PADA SISWA KELAS VII SMPN 4 BENAI KECAMATAN BENAI - Osa Rizalsyam (PGRI Provinsi Riau, 2021)
Student learning activities in the science learning process for class VII SMPN 4 Benai, Kuansing Regency are still lacking in learning through practicum. Even if the practice is only a demonstration carried out by the teacher accompanied by the lecture method, the learning process is teacher-centered, students are more passive, less creative, lack the initiative to develop their own potential. so that boredom and boredom arise in students which in turn causes low student learning outcomes.. Science learning outcomes are the abilities that students have after they get a learning experience. This research was conducted in two cycles, each cycle consisting of four stages, namely planning, implementation, observation and reflection. To obtain research data, an observation sheet filled in by the observer was used and a learning outcome test given at the end of the cycle. Data on student learning activities were analyzed by determining the number and percentage of students involved in each meeting. The increase in learning outcomes is seen from the number of students who complete at the end of the cycle. The results showed that learning activities and student learning outcomes experienced an increase after the action was carried out for two cycles. At the end of the second cycle, the students who achieved completeness reached 87.27%. From this data it can be concluded that the use of inquiry strategies can increase student activity and learning outcomes.